2009
DOI: 10.1007/s11104-009-9999-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of cotyledon metabolism in the establishment of quinoa (Chenopodium quinoa) seedlings growing under salinity

Abstract: A growth chamber experiment was conducted to assess the effect of salinity on emergence, growth, water status, photosynthetic pigments, osmolyte accumulation, and ionic content of quinoa seedlings (Chenopodium quinoa). The aim was to test the hypothesis that quinoa seedlings are well adapted to grow under salinity due to their ability to adjust the metabolic functionality of their cotyledons. Seedlings were grown for 21 days at 250 mM NaCl from the start of the germination. Germination percentage and cotyledon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 61 publications
9
62
3
3
Order By: Relevance
“…The results presented in Figure 1, Tables 3 and 4 are agreement with Ana Maria et al (2010) who decided that, relative water content, chlorophyll, carotenoids, lipids, and proteins traits in quinoa seedlings were significantly lower under salinity (250 mM NaCl) and Eisa et al (2012) who reported that, the net photosynthesis rates of quinoa plant were greatly decreased by high salinity, being 28% of initial control values at 500 mM NaCl also they reported that salt-induced growth reduction is presumably due to low photosynthetic supply as a Vol. 7, No.…”
Section: Effect Of Salinity On the Vegetative And Physiological Traitssupporting
confidence: 87%
See 1 more Smart Citation
“…The results presented in Figure 1, Tables 3 and 4 are agreement with Ana Maria et al (2010) who decided that, relative water content, chlorophyll, carotenoids, lipids, and proteins traits in quinoa seedlings were significantly lower under salinity (250 mM NaCl) and Eisa et al (2012) who reported that, the net photosynthesis rates of quinoa plant were greatly decreased by high salinity, being 28% of initial control values at 500 mM NaCl also they reported that salt-induced growth reduction is presumably due to low photosynthetic supply as a Vol. 7, No.…”
Section: Effect Of Salinity On the Vegetative And Physiological Traitssupporting
confidence: 87%
“…There is also evidence to support the view that salt tolerance is a complex physiological trait affecting entirely the plant's life (Flowers, 2004). In addition, the quinoa plant is reported to be tolerant to drought (Garcia et al, 2007), and also resists frost before the flower-bud formation stage (Jacobsen et al, 2005) and salinity (Ruffino et al, 2010;Hariadi et al, 2011). However, the definition of indicators that plant breeders might apply in open field to improve quinoa, for its tolerance or adjustment to saline environments, is still a matter of debate (Razzaghi et al, 2011a).…”
Section: Introductionmentioning
confidence: 95%
“…The many salt-related studies have ranged from seed germination effects to whole plant growth, physiological to anatomical changes, biochemical composition differences to biomass and yield reduction and covered a very wide range of plant species (Niazi et al, 1987;Katerji et al, 1994;Poljakoff-Mayber et al, 1994;Villiers et al, 1994;Rogers et al, 1995;Reinhardt and Rost, 1995 a, b;Zidan and Elewa, 1995;Huang and Redmann, 1995;Wahid et al, 1998;Croser et al, 2001;Al-Mutawa, 2003;Turhan and Ayaz, 2004;Song et al, 2008;MaiaI et al, 2010;Ruffino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mannitol, proline and myo-inositol are the compatible solutes present in quinoa (Ruffino et al, 2010) with the ability to scavenge ROS (Szabados and Savouré, 2010). Tolerance of quinoa to salinity may be credited to its efficient retention of K + (Ruffino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Tolerance of quinoa to salinity may be credited to its efficient retention of K + (Ruffino et al, 2010). Salinity caused a decrease in transpiration and thus gas exchange in quinoa (Sanchez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%